Bleeding Through a Pandemic: Women’s Lived Experiences with Heavy Menstrual Bleeding During the COVID-19 Pandemic - Anto-Ocrah M; Affan NJ; Vempalli H; Chen M; Niyomugabo C; Glantz JC; Hollenbach S (International Journal of Women's Health)
Martina Anto-Ocrah,1,2 Nabeeha Jabir Affan,2 Hemika Vempalli,1 Michael Chen,3 Celestin Niyomugabo,4 J Christopher Glantz,5 Stefanie Hollenbach5 1Division of General Internal Medicine, University of Pittsburgh School of Medicine, Pittsburgh, PA, USA; 2Department of Epidemiology, University of Pittsburgh School of Public Health, Pittsburgh, PA, USA; 3JSI Research & Training Institute, Boston, MA, USA; 4VONSUNG, Kigali, Rwanda; 5Department of Obstetrics and Gynecology, University of Rochester School of Medicine and Dentistry, Rochester, NY, USACorrespondence: Martina Anto-Ocrah, Email Maa509@pitt.eduIntroduction: Heavy menstrual bleeding (menorrhagia) affects 10 million reproductive-age women. Stress is a mechanism for menstrual disorders, and during the COVID-19 pandemic, women reported worsening premenstrual and menstrual symptoms. We hypothesized that there would be a positive association between COVID stress and menorrhagia and a negative association between menorrhagia and mental health. A third objective was to explore women’s lived experiences with menorrhagia during the pandemic, including menstrual pain and impact on socialization, sex life, and product use.Methods: This was a secondary data analyses of a cross-sectional study that recruited adult women between the ages of 18– 45 years using Dynata, a survey sampling company that maintains a web panel of survey takers across the United States. Menorrhagia was assessed with the Aberdeen Menorrhagia Severity Scale (AMSS), COVID stress with the COVID-19 Pandemic-related Perceived Stress Scale (PSS-10-C), and mental health with the Mental Health Continuum Scale (MHC-SF). We grouped the participants into mild menorrhagia (AMSS score 0– 33)” and moderate/severe menorrhagia (AMSS score 34– 100) and compared the outcomes using descriptive statistics, correlations, and linear regression.Results: The survey was conducted in May 2021. Among 1,037 initial responses, 360 naturally cycling women met the study eligibility criteria. Women with heavy bleeding reported more COVID-stress than those without heavy bleeding (p < 0.01) and heavy bleeding intensified with increasing COVID-related stress (adj. β = 0.37, 95% CI: 0.21, 0.53). Adjusting for baseline depression, mental health worsened as heavy bleeding increased (adj. β = − 0.1, 95% CI: − 0.24, − 0.03). Compared to those without heavy bleeding, women with heavy bleeding were more likely to report severe pain and bed confinement, less socialization, a negative impact on sex life, and greater use of menstrual products.Conclusion: COVID-related stress affects menstrual physiology and also complex interactions between life-course, social functioning, financial strain, and psychological stress. Our findings support increased awareness of these interactions in gynecologic care during a global pandemic.Keywords: women’s health, COVID, menstruation, menorrhagia, heavy bleeding, COVID stress, COVID risk, menstrual cup, pandemic